Do Foreign Firms Really Pay Higher Wages? : Evidence from Different Estimators - Pedro Silva Martins (Institute for the Study of Labor (IZA), 2004)
We contribute to the literature on Foreign Direct Investment and labour markets by examining wage differentials between domestic and foreign firms, drawing on a large Portuguese matched employer-employee panel. Using OLS, the foreign-firm premium is large and significantly positive but falls substantially when firm and worker controls are added. Moreover, the premium also does not vary monotonically with foreign control, it increases along the wage distribution and it is generally insignificant when using propensity score matching. Finally, using differences-in-differences, we find lower wage growth for workers in domestic firms that are acquired by foreign investors, a result that holds when combining differences-in-differences and propensity score matching. Overall, our evidence suggests that the commonly-documented OLS premium cannot be interpreted as a causal impact.
Keywords: C23; J31; F23; 330; FDI; wages; matched employer-employee data; propensity score matching; Portugal; Lohnstruktur; Multinationales Unternehmen; Unternehmen; Direktinvestition; Schätzung; Portugal